THE STUDY OF THERMAL EFFECT ON THE SURFACE PROPERTIES OF GAMMA-ALUMINA SYNTHESIED FROM KANKARA KAOLIN. (Nigerian Journal of Technology, 2015)
Gamma alumina is a good material for catalyst support and its surface properties is of great importance. In this study the gamma-alumina (?-Al2O3) synthesized to be used as catalyst support for zeolite catalyst was obtained by calcination of ammonium alum an intermediate product prepared from kaolin which was sourced from Kankara, Katsina, Nigeria. The surface properties were determined using BET technique. BET specific surface area of gamma alumina produced at 825°C for soaking time of 3h was 120m2/g while at 850°C for soaking time of 4h the surface area was 140m2/g. The pore size and pore volume range from 15nm to 25nm and 0.5cm3/g to 0.8cm3/g respectively. The XRD pattern obtained at 825°C and 875°C calcination temperatures conformed to the standard pattern of gamma-alumina, having the strong peaks at Bragg angles of 67, 46, 39 and 38°. The SEM image showed clearly the plate-like structure of gamma alumina. Thus kankara kaolin is a promising material for the production of gamma alumina. http://dx.doi.org/10.4314/njt.v35i1.11